2019
DOI: 10.1186/s12957-019-1588-6
|View full text |Cite
|
Sign up to set email alerts
|

Tumor budding for predicting prognosis of resected rectum cancer after neoadjuvant treatment

Abstract: BackgroundRectum cancer is a type of colorectal cancer. Its etiology and etiopathogenesis are similar to other colon diseases. We aimed to evaluate the tumor budding for predicting prognosis of resected rectum cancer patients.MethodsWe retrospectively collected the data of 75 operated rectum adenocarcinoma patients who were treated neoadjuvant chemoradiotherapy between 2013 and 2018 in Umraniye Research and Training Hospital and Acıbadem University Medical Oncology Outpatient Clinic. Tumor budding was investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
(31 reference statements)
0
11
1
1
Order By: Relevance
“…Consistently with the results reported by others, 9 our data support only LVI as a predictor of DFS, whereas we did not find any association between yp N/PNI and DFS. Finally, the association between PNI and tumour budding with OS or DFS proposed by other authors 8,9,24 is not confirmed by our results. Low numbers may have eventually prevented from reaching any significant difference in survival between patients with and without the reported parameters.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Consistently with the results reported by others, 9 our data support only LVI as a predictor of DFS, whereas we did not find any association between yp N/PNI and DFS. Finally, the association between PNI and tumour budding with OS or DFS proposed by other authors 8,9,24 is not confirmed by our results. Low numbers may have eventually prevented from reaching any significant difference in survival between patients with and without the reported parameters.…”
Section: Discussioncontrasting
confidence: 99%
“…Tumour regression grade (TRG), intended as the histological modifications induced by NA‐CRT, is gaining acceptance as predictor of therapy success and survival 7 and is increasingly considered together with several other factors, including tumour budding, perineural invasion (PNI), lymphovascular invasion (LVI) and lymph node metastasis, in LARC prognosis assessment 8,9 . Nevertheless, at present, the real impact of TRG on prognosis with respect of other variables is still poorly studied and under debated 10,11 …”
Section: Introductionmentioning
confidence: 99%
“…Budding has been shown to be a negative prognostic factor for survival in different kinds of study designs and for a broad range of cut-offs. However, most of the previous studies could demonstrate effects on survival only in univariate analysis or limited to disease free survival [15][16][17][18][19]. Including patients with complete response in the analysis appeared to attenuate the prognostic impact of tumor budding.…”
Section: Discussionmentioning
confidence: 95%
“…Budding has been described as a prognostic feature after chemoradiotherapy in rectal cancer patients in several publications with the general limitation of a retrospective study design. In previous studies, budding was reported in 10.1-63.2% of cases due to different methodologies used for evaluation [3,[15][16][17][18][19][20]. Budding has been shown to be a negative prognostic factor for survival in different kinds of study designs and for a broad range of cut-offs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in CRC, tumor cells undergoing EMT are histologically represented by the presence of tumor buds defined as single cells or small clusters of dedifferentiated tumor cells at the invasive front 19 , 20 . Tumor budding is a predictor of lymph node metastasis, vascular and lymphatic invasion, distant metastasis, local recurrence, and poor disease-specific survival duration 21 , 22 . Moreover, the Union for International Cancer Control (UICC) identifies tumor budding as a critical and additional prognostic factor 23 .…”
Section: Introductionmentioning
confidence: 99%